Review of indoor localization techniques - Din M.M.; Jamil N.; Maniam J.; Mohamed M.A. (Science Publishing Corporation Inc, 2023)
Global Positioning System (GPS) has practically solved the problem of outdoor localization. However, limitation of GPS leads to a chal-lenge for developing a new tracking system for indoor environment. Hence, the demand for accurate indoor localization services has become important. Until now, researches related to IPS are still being conducted with the objective to improve the performance of posi-tioning techniques. This paper provides a comprehensive review of indoor localization techniques and stimulate new research effort in this field. Current existing indoor localization system that used for tracking objects were reviewed along with some further discussion to design a better indoor localization technique. 2016 Authors.